Left-right judgment of haptic stimuli representing the human hand - Maria Luiza Rangel (Psychology & Neuroscience, 2010)
The handedness recognition of visually perceived body parts engages motor representations that are constrained by the same biomechanical factors that limit the execution of real movements. In the present study, we used small plastic cutouts that represented the human hand to investigate the properties of mental images generated during their haptic exploration. Our working hypothesis was that any handedness recognition task that involves body parts depends on motor imagery. Forty-four blindfolded, right-handed volunteers participated in a handedness evaluation experiment using their index finger to explore either the back or palm view of a haptic stimulus that represented the human hand. The stimuli were presented in four different orientations, and we measured the subjects' response times. Our results showed that stimulus configurations that resemble awkward positions of the human hand are associated with longer response times (p < .006), indicating that the haptic exploration of stimuli that represent body parts also leads to motor imagery that is constrained by biomechanical factors.